A long-term survivor of clear cell sarcoma-like tumor of the gastrointestinal tract with liver metastasis: a case report - Takuhisa Okada; Yasumitsu Hirano; Shintaro Ishikawa; Hiroka Kondo; Toshimasa Ishii; Shigeki Yamaguchi (Surgical Case Reports)
Abstract Background Clear cell sarcoma-like tumor of the gastrointestinal tract (CCSLTGT) is extremely rare. It is a mesenchymal neoplasm that usually forms in the small intestine of adolescents and young adults, is prone to local recurrence and metastasis, and has a high mortality rate. We report a patient with CCSLTGT with lymph node- and liver metastases, who continues to survive 6 years after initial surgical resection. Case presentation A 38-year-old woman presented with lightheadedness. Laboratory analysis revealed anemia (hemoglobin, 6.7 g/dL), and enhanced computed tomography (CT) demonstrated a mass in the small intestine, about 6 cm in diameter, with swelling of 2 regional lymph nodes. Double-balloon small intestine endoscopic examination revealed a tumor accompanied by an ulcer; the biopsy findings suggested a primary cancer of the small intestine. She was admitted, and we then performed a laparotomy for partial resection of the small intestine with lymph node dissection. Pathologic examination revealed CCSLTGT with regional lymph node metastases. About 3 years later, follow-up CT revealed a single liver metastasis. Consequently, she underwent a laparoscopic partial liver resection. Histopathologic examination confirmed that the liver metastasis was consistent with CCSLTGT. It has now been 3 years without a recurrence. Conclusion Repeated radical surgical resection with close follow-up may be the only way to achieve long-term survival in patients with CCLSTGT.